Crack and deformation behavior of composite beams using partial‐depth precast concrete units. Issue 1 (26th May 2020) - Mager, Matthias; Geißler, Karsten
Abstract: In ranges with negative moments, crack formation influences the structural behavior of statically indeterminate composite beams under service conditions. Composite beams with partial‐depth precast concrete units show some particularities, which cannot be described accurately using the established methods of calculation. This article presents methods of calculation, which can be used to cover the specific structural behavior and describe crack formation, crack widths and deformations realistically.